CapCut dan Canva sebagai Media Efektif Pembelajaran Visual di SMP Kanisius Sumber - Maria Atik Sunarti Ekowati; Moyo Hady Poernomo; Gabriel Silvano; Unggul Widya Saputra (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
This Community Service Program (PkM) was initiated based on the need for innovative visual learning media that can engage students and improve concept understanding. Students at SMP Kanisius Sumber show high interest in digital-based learning, yet teachers face challenges in creating interactive and engaging visual content. This program offers a solution through training and mentoring in the use of CapCut and Canva applications as creative and accessible visual learning media.The aim of this program is to enhance the competence of both teachers and students in creating and utilizing digital-based visual learning materials. The implementation methods included workshops, hands-on training, content creation sessions, and outcome evaluations. The discussion reveals a high level of enthusiasm among participants, and a noticeable improvement in their ability to produce educational visual content using CapCut and Canva. The final results show an increase in learning effectiveness and more active teacher-student interaction. The targeted outcomes of this PkM include digital learning media products made with CapCut and Canva, activity documentation, and a scholarly article intended for publication in a community service journal.